The bay' al-'inah controversy in Malaysian Islamic banking - Shaharuddin A. (2024)
The current practice of Islamic banking in Malaysia has been criticised as insufficiently different from conventional banking. One of the foci of this criticism is the application of bay' al-'inah, sales contract with immediate repurchase, in creating a number of so-called Islamic financing products. The present article examines the classical jurists' assessment of the contract and then evaluates the justifications of the Malaysian National Shari'ah Advisory Committee (NSAC). As a case study, this article analyses the application of bay' al-'inah in inventing a credit card of Bank Islam Malaysia Berhad. Understanding the NSAC's justifications will help us comprehend their methodology and approach when approving other Islamic banking products in the country. Koninklijke Brill NV, Leiden, 2012.